NOVEL ORANG-ORANG PROYEK KARYA AHMAD TOHARI (Kajian Analisis Wacana Kritis Michel Foucault) - Achmad Fathoni (EDU-KATA, 2014)
The aim of study was to describe the authority of discursive practice of OrdeBaru in novel Orang – orang Proyek by Ahmad Tohari, the roles of a literary work as a resistance to the hegemony power of OrdeBaru in novel Orang – orang Proyek by Ahmad Tohari, the discursive strategy as an effort to frame knowledge or desire in novel Orang – Orang Proyek by Ahmad Tohari, the power relation in novel Orang – Orang Proyek by Ahmad Tohari.The methodology of this research is descriptive qualitative by using the theory of Michael Foucault’s Critical Discourse Analysis. The result of this study shows that the power of OrdeBaru wants to form a development by moving the normalization with party similarity that tends to do a dishonest political practice and cause corruption. Novel Orang –Orang Proyek by Ahmad Tohari has a role as a tool to fight the authority the discursive of OrdeBaru which near with dishonest politic, corruption, and repressive will cause the resistance to the hegemony power. Writing is a discursive strategy that Ahmad Tohari did to apply the counter-hegemony to the government through his novel. Power relation will proof that there is a knowledgeproduction to strengthen the authority and the truth.